Trajectories of Binge Drinking Behavior across Adolescence among Juvenile Offenders and the Role of ADHD for Predicting Development. Issue 6 (3rd June 2018) - Wojciechowski, Thomas W.
ABSTRACT: Binge drinking has been linked to numerous health issues. Juvenile offenders may be at increased risk for binge drinking. ADHD has been demonstrated to be a predictor of substance use. The development of binge drinking behavior and the role of ADHD for predicting this development among this population has not yet been explored. This research uses group-based trajectory modeling to describe binge drinking development. Multinomial logistic regression is used to examine the role of ADHD for predicting development. Results indicate that an 8-group model fits the data and that ADHD predicts assignment to the High Chronic trajectory group.